Characteristic and Self-Life Test of Food Bar with Combination of White Millet, Snakehead Fish and Soy Flour - Lukita Purnamayati; Raden Baskara Katri Anandito; Siswanti Siswanti; Edhi Nurhartadi (Universitas Sebelas Maret, 2019)
Emergency food is needed when a disaster occurs. Emergency conditions encourage the provision of food that is ready to eat with sensory properties that can be accepted by the community, has sufficient nutrient content to meet the body's caloric needs and is resistant during storage. This study aims to obtain the best formulas of the food bar based on the parameters observed, namely sensory, chemical, total caloric, and aw as well as its shelf life estimation with the Accelerated Shelf Life Test. Food bar was made from white millet flour and fish koya that was made from snakehead fish and soy flour. Intermediate moisture food (IMF) applied in this study with the initial formulation was determined using mass equilibrium. The effectiveness test was used to determine the best formula based on all observed parameters. The results showed that the best food bar formula was formula F2, which has a chemical composition consisting of moisture content (20,99±0,21%); ash (3,45±0,35%); fat (18,10±0,13%); protein (12,24±0,28%); and carbohydrates (45,22±0.32%), aw (0,76±0,01); and total calories (per 50 g) was 232,04±1,96 kcal. The shelf life of food bar F2 was 19 days. Based on the results obtained, the total calories produced from the best formula have not met emergency food calorie standards.